Seeking and Ensuring Interdependence: Desiring Commitment and the Strategic Initiation and Maintenance of Close Relationships. (January 2020) - Tan, Kenneth; Agnew, Christopher R.; Hadden, Benjamin W.
The current research offers and examines the concept of commitment desirability, defined as the subjective desire to be involved in a committed romantic relationship at a given time. In pursuing their desire for a committed romance, how do individuals high in commitment desirability strategically ensure success? We suggest that high perceived partner commitment is sought by individuals who themselves desire to be involved in a committed relationship. In three studies involving individuals both currently involved and not involved in a relationship, we found support for the hypothesized interactive effect of commitment desirability and perceived partner commitment, such that greater commitment desirability was associated with more positive relationship outcomes, especially when partners were perceived to be high in commitment. The present research suggests that commitment desirability is a meaningful predictor of relationship attitudes and behaviors. Implications for understanding relationship commitment as well as future research directions are discussed.